Evaluation of an electric turbo compound system for SI engines: A numerical approach. (15th January 2016) - Pasini, Gianluca; Lutzemberger, Giovanni; Frigo, Stefano; Marelli, Silvia; Ceraolo, Massimo; Gentili, Roberto; Capobianco, Massimo
Highlights: Electric Turbo Compound (ETC) can improve exhaust gas energy recovery in Internal Combustion Engine (ICE). Models of a SI-ICE with ETC and whole vehicle were created using 1-D numerical codes. At ICE operating fixed point the ETC is not beneficial over a conventional turbocharger with appropriate turbine sizing. ETC can slightly improve overall efficiency when the ICE must provide variable power output. ETC application is more advantageous in motorway cycles, since the engine works at high loads and speeds. Abstract: In a medium term scenario hybrid powertrain and Internal Combustion Engine (ICE) downsizing represent the actual trend in vehicle technology to reduce fuel consumption and CO2 emission. Concerning downsizing concept, to maintain a reasonable power level in small engines, the application of turbocharging is mandatory both for spark ignited (SI) and compression ignited (CI) engines. Following this aspect, the possibility to couple an electric drive to the turbocharger (electric turbo compound) to recover the residual energy of the exhaust gases is becoming more and more attractive, as demonstrated by several studies around the world and by the current application in the F1 Championship. The present paper shows the first numerical results of a research program in collaboration between the Universities of Pisa and Genoa. This first study is focused on the evaluation of the benefits resulting from the application of an ETC (Electric Turbo Compound) to a small twin-cylinder SI engine (900 cm 3 ). Starting from the experimental maps of two turbines and one compressor, the complete model of a turbocharged engine was created using the AVL BOOST one-dimension code. The numerical activity then moves to the whole vehicle/powertrain modelling, considering three driving cycles and two different vehicle configurations, in order to verify the effectiveness of the proposed ETC solution. Results show that the adoption of ETC is not advantageous if used for a conventional turbocharger turbine, if the target is to optimize the overall efficiency in one specific operating point of the ICE, like in the case of range-extended electric vehicles. Besides, ETC can slightly improve the average overall efficiency when the ICE must provide variable power output, as in the case of conventional or hybrid vehicles. However, the major benefits coming from ETC are the boost range extension in the lowest engine rotational speed region and a possible reduction of turbo lag, which are key points in parallel-hybrid and especially in conventional vehicles. Concerning the whole vehicle/powertrain simulation, first results show that the ETC does not improve fuel economy of the smaller vehicle, especially when employed in urban cycles. The ETC is much more advantageous in the case of the larger vehicle, particularly when extra-urban roads or motorways are considered.